DEVELOPMENT OF ONLINE-BASED ARBEITSBLATT ON LIVEWORKSHEETS WITH ‘HOBBY’ THEME FOR CROSS-MAJOR GERMAN LANGUAGE ClASS ON XII AT SMA LABORATORIUM UM - Lintang Nur Hidayati (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2023)
The purpose of this research is to develop liveworksheets-based Arbeitsblatt that can help students of XII cross-major class learn German about hobbies independently with a blended learning system. The development model used is the ADDIE development model. The type of data in this study is qualitative data supported by quantitative data obtained through a questionnaire. The developed Arbeitsblatt got a score of 93.75% for media feasibility and a score of 77% for material feasibility. Based on the data analysis of the questionnaire results obtained from students, the student's response to Arbeitsblatt as a whole reached a score of 89.92% for attractiveness, understanding, and convenience aspects. Thus it can be concluded that Arbeitsblatt based liveworksheets is feasible and can be used by students to learn German on a hobby theme independently.Keywords: Online-Based Arbeitsblatt on Liveworksheets, Hobby Theme, Cross-Major German Language Class